The fission yeast chromo domain encoding gene chp1(+) is required for chromosome segregation and shows a genetic interaction with alpha-tubulin. - Doe, C; Wang, G; Chow, C; Fricker, M; Singh, P; Mellor, E (1998)
In eukaryotes, the segregation of chromosomes is co-ordinated by the centromere and must proceed accurately if aneuploidy and cell death are to be avoided. The fission yeast centromere is complex, containing highly repetitive regions of DNA showing the characteristics of heterochromatin. Two proteins, Swi6p and Clr4p, that are associated with the fission yeast centromere also contain a chromo (chromatin organisation modifier) domain and are required for centromere function. We have analysed a novel fission yeast gene encoding a putative chromo domain called chp 1(+) (chromo domain protein in Schizosaccharomyces p ombe ). In the absence of Chp1p protein, cells are viable but show chromosome segregation defects such as lagging chromosomes on the spindle during anaphase and high rates of minichromosome loss, phenotypes which are also displayed by swi 6 and clr 4. A fusion protein between green fluorescent protein (GFP) and Chp1p, like Swi6p, is localized to discrete sites within the nucleus. In contrast to Swi6p and Clr4p, Chp1p is not required to repress silent mating-type genes. We demonstrate a genetic interaction between chp 1(+) and alpha-tubulin ( nda 2(+)) and between swi 6(+) and beta-tubulin ( nda 3(+)). Chp1p and Swi6p proteins may be components of the kinetochore which captures and stabilizes the microtubules of the spindle.